Neues Museum : Staatliches Museum für Kunst und Design in Nürnberg. - Grisebach, Lucius; Heyden, Thomas; Kliege, Melitta; Strasser, Josef; Suk, Birgit; Neuesmuseum - Staatliches Museum für Kunst und Design, Nürnberg (München : Prestel Verlag, 2000)
Aarnio, Eero ; Angermann, Peter ; Antes, Horst ; Arad, Ron ; Armando ; Balkenhol, Stephan ; Baselitz, Georg ; Beltzig, Günter ; Beuys, Joseph ; Bijl, Guillaume ; Casati, Cesare ; Charbonneaux, Philippe ; Cocteau, Jean ; Delvoye, Wim ; Dietz, Matthias ; Dimitrijevic, Braco ; Dixon, Tom ; Drocco, Guido ; Droog Design ; Eames, Charles & Ray ; Eppich, Egon ; Fauxpas ; Federle, Helmut ; Fruhtrunk, Günter ; Fuller, Paul ; Ghyczy, Peter ; Gilardi, Piero ; Graevenitz, Gerhard von ; Graubner, Gotthard ; Grcic, Konstantin ; Gugelot, Hans ; Gursky, Andreas ; Heidenreich, Fritz ; Honert, Martin ; Horn, Roni ; Inflate ; Ive, Jonathan ; Jacobsen, Arne ; Kagan, Vladimir ; Kantor, Tadeusz ; Kern, Stephan ; Kiecol, Hubert ; King, Perry A. ; Knaupp, Werner ; Knifer, Julije ; Kolar, Jiri ; Koppel, Henning ; Kosuth, Joseph ; Kuehn, Gary ; Landes, Heinz ; Lébovici, Yonel ; Leccia, Ange ; Lindner, Richard ; Lomazzi, Paolo ; Long, Richard ; De Lucchi, Michele ; Lucini, Ennio ; Maciunas, George ; Mangiarotti, Angelo ; Marotta, Gino ; Maurer, Dora ; Maurer, Ingo ; McCaslin, Matthew ; Mello, Franco ; Millares, Manolo ; Möbus, Christiane ; Mollino, Carlo ; Morassutti, Bruno ; Morellet, François ; Noguchi, Isamu ; Paik, Nam June ; Panton, Verner ; Parigi, Vittorio ; De Pas, Jonathan ; Penck, A.R. ; Pesce, Gaetano ; Pfahler, Georg Karl ; Piene, Otto ; Polke, Sigmar ; Ponzio, Emanuele ; Porsche, Ferdinand ; Prina, Nani ; Rams, Dieter ; Rancillac, Bernard ; Rheinsberg, Raffael ; Riley, Bridget ; Ruff, Thomas ; Ruthenbeck, Reiner ; Sachs, Rolf ; Sarpaneva, Timo ; Schoonhoven, Jan ; Schütte, Thomas ; Smith, Leon Polk ; Sonnier, Keith ; Sottsass, Ettore ; Starck, Philippe ; Stiletto ; Studio 65 ; Stupica, Gabrijel ; Trockel, Rosemarie ; Umeda, Masanori ; Urbino, Donato d' ; etc.
Duits
boek